Social emotional competence and science outcomes in a low-income preschool sample: a concurrent and longitudinal analysis - Mahaffy, Everett; Zehner, Tracy M.; Westerberg, Lauren; Purpura, David James; Schmitt, Sara A. (Frontiers in Developmental Psychology, 2026)
Children's early science knowledge is predictive of later academic outcomes, but little work has characterized the factors that shape early science development. In light of theoretical and empirical evidence highlighting the importance of social processes in science learning, the aim of this study was to examine concurrent and longitudinal relations between children's social skills and science core knowledge across 1 year of preschool. The sample consisted of 124 preschool-aged children (43% female; 70% non-white) from families at or below 127% of the federal poverty level. Using linear regression models, we examined whether teacher-rated social skills in the fall of preschool predicted science core knowledge concurrently (in the fall) and longitudinally (in the spring). After adjusting for child demographic factors, executive function, and vocabulary knowledge, no significant associations between children's social skills and science core knowledge emerged. As the first study to investigate this topic, the present study contributes to an emerging literature base. Implications for future research, including generalizability and measure selection, are discussed.